2022
DOI: 10.1111/nph.17916
|View full text |Cite
|
Sign up to set email alerts
|

A MADS‐box gene with similarity to FLC is induced by cold and correlated with epigenetic changes to control budbreak in kiwifruit

Abstract: Temperate perennials require exposure to chilling temperatures to resume growth in the following spring. Growth and dormancy cycles are controlled by complex genetic regulatory networks and are governed by epigenetic mechanisms, but the specific genes and mechanisms remain poorly understood.To understand how seasonal changes and chilling regulate dormancy and growth in the woody perennial vine kiwifruit (Ac, Actinidia chinensis), a transcriptome study of kiwifruit buds in the field and controlled conditions wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 118 publications
4
35
0
Order By: Relevance
“…The expression levels of FLC2 were positively and negatively correlated with the pattern of H3K4me3 and H3K27me3 levels, respectively (Figure 2a; Table S4), suggesting that the transcription of FLC2 , a key factor of the quiescent state, is regulated by these modifications. In addition, we observed that many RNA‐seq reads map to intronic regions for all FLC loci, suggesting the existence of non‐coding RNAs similar to Arabidopsis COOLAIR and COLDAIR , which modulate the epigenetic silencing of FLC , and to kiwifruit long non‐coding RNAs, which regulate chromatin state at an FLC ‐like gene (Heo & Sung, 2011; Swiezewski et al., 2009; Voogd et al., 2021). We detected the highest levels of H3K27me3 modification at the DAM2 , DAM4 , DAMb , FLC3 , and FLC4 loci at the BB stage, likely to maintain their repressed transcriptional state, as with Arabidopsis FLC (Buzas et al., 2011, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…The expression levels of FLC2 were positively and negatively correlated with the pattern of H3K4me3 and H3K27me3 levels, respectively (Figure 2a; Table S4), suggesting that the transcription of FLC2 , a key factor of the quiescent state, is regulated by these modifications. In addition, we observed that many RNA‐seq reads map to intronic regions for all FLC loci, suggesting the existence of non‐coding RNAs similar to Arabidopsis COOLAIR and COLDAIR , which modulate the epigenetic silencing of FLC , and to kiwifruit long non‐coding RNAs, which regulate chromatin state at an FLC ‐like gene (Heo & Sung, 2011; Swiezewski et al., 2009; Voogd et al., 2021). We detected the highest levels of H3K27me3 modification at the DAM2 , DAM4 , DAMb , FLC3 , and FLC4 loci at the BB stage, likely to maintain their repressed transcriptional state, as with Arabidopsis FLC (Buzas et al., 2011, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, even in Arabidopsis , mutations that substantially affect flowering time in laboratory experiments do not necessarily show large differences in flowering time in the field ( 27 ). Thus, control of flowering in winter annuals may more closely resemble that of perennials than summer annual species, which also show bud dormancy control via FLC -like genes and its partner SHORT VEGETATIVE PHASE ( 28 30 ). In perennial crops failure to break bud dormancy can result in yield losses via problems in bud break, flower abscission, floral organ, and fruit abnormalities ( 31 ).…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, three paralogous FLC clades seem to exist in core eudicots, with one member each in the tea plant genome; we named these genes CsFLC1, CsFLC2 and CsFLC3. Although CsFLC1 is only 32% homologous to Arabidopsis FLC, it is 56% homologous to and collinear with the AcFLCL (Acc05562) gene recently reported in the closely related kiwifruit (Voogd et al, 2022). Moreover, CsFLC2 is homologous and shares gene collinearity with the kiwifruit genes Acc14299 and Acc33776 (data not shown).…”
Section: Identification Of Csflc-like Genes In the Tea Genomementioning
confidence: 69%
“…and kiwifruit ( Actinidia chinensis Planch. ), where it is highly expressed during dormancy (Soichiro et al ., 2019; Voogd et al ., 2022). However, transgenic kiwifruit plants overexpressing AcFLCL displayed earlier budbreak times (Voogd et al ., 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation